INDUKSI TUNAS JERUK SIAM (Citrus nobilis Lour.) ASAL KAMPAR DENGAN PEMBERIAN BENZIL AMINO PURINE (BAP) SECARA IN VITRO - Rahmahayu '; Siti Fatonah; Mayta Novaliza Isda (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Citrus (Citrus nobilis Lour.) from Kampar is one of primary commodities from Riau province. However, virus attacks cause citrus plants become sick and even died, therefore it is difficult to find the healthy citrus plants. In order to recover this condition, it is necessary to provide citrus seedlings in large quantities. One alternative to provide citrus seedling in large quantities is through tissue culture technique (in vitro culture). This study aimed to find out the effect of benzil amino purine (BAP) and to determine the optimal concentration of BAP in inducing shoot of citrus. This experiment was designed using a randomized block design (RBD) with various concentrations of BAP. The results showed that the treatment with 1 mg/l BAP was the best in inducing the number of shoots (3 shoots/explant) and treatment with 0.5 mg/l BAP was the best in generating shoot length (3.11 cm) and number of leaves (5.26 piece/shoot).